Handgrip Strength has Declined Among Adults, Particularly Males, from Shanghai Since 2000 - Wang, Dao; Liu, Yang; Lang, Justin J.; Klug, Marilyn G.; McGrath, Ryan; Tomkinson, Grant R. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Handgrip strength (HGS) is an excellent marker of general strength capacity and health among adults. We aimed to calculate temporal trends in HGS for adults from Shanghai between 2000 and 2020. Methods Adults aged 20–59 years from Shanghai, China, were included. Representative cross-sectional HGS data (n = 127,756) were collected in 2000, 2005, 2010, 2014, and 2020. HGS was measured using isometric dynamometry and was adjusted for body size (i.e., height-squared). Trends in mean adjusted HGS were calculated using general linear models with adjustments for age, sex, location, occupation, blood pressure, and exercise time. Trends in distributional characteristics were described visually and calculated as the ratio of coefficients of variation (CVs). Results We found a significant, small decline in mean adjusted HGS (effect size (ES) [95%CI]: −0.21 [−0.22, −0.20]) since the year 2000. Negligible temporal differences were found across age, location, and occupation groups, with a 2.8-fold greater decline for men than for women. Overall, distributional variability declined negligibly (ratio of CVs [95% CI]: 0.92 [0.91, 0.93]). We also observed a negligible trend (ES < 0.20) in distributional asymmetry among adults with low adjusted HGS (below the 25th percentile) and a small decline (ES = 0.20−0.49) in adults with high adjusted HGS (above the 75th percentile). Conclusions There was a recent small decline in adjusted HGS for adults from Shanghai, which was greater for men than for women and nonuniform across the population. A decline in adjusted HGS may represent a decline in the general/functional health of the population.

Key Points Mean body size-adjusted handgrip strength (HGS) among adults from Shanghai (aged 20–59-years) declined between 2000 and 2020. The decline in adjusted HGS was 2.8-fold larger for men than for women, which suggests that the sex gap in adjusted HGS is closing. There was a smaller temporal decline for adults with low adjusted HGS than for adults with high adjusted HGS. A decline in adjusted HGS may represent a similar decline in the general and functional health of the population.